EFEKTIVITAS IMPLEMENTASI PROGRAM PUPUK BERSUBSIDI OLEH DINAS PERTANIAN KABUPATEN SIAK (STUDI KASUS KELOMPOK TANI KECAMATAN TUALANG) - Muhammad Wahyu; Adianto Adianto (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The phenomenon of fertilizer prices which far exceeds the highest retail price from the government and the difficulty of getting subsidized fertilizers (rare) so that in one year they only get a few times with minimal amounts as well as the presence of individuals seeking personal gain, which makes researchers interested in researching the effectiveness of the implementation of the Subsidized Fertilizer Program. By the Agriculture Service of Siak Regency (Case Study of Farmer Groups in Tualang District). The purpose of this study was to determine the effectiveness of the implementation of the Subsidized Fertilizer Program in Siak Regency and to determine the factors hindering the effectiveness of the implementation of the Subsidized Fertilizer Program in Siak Regency. This study uses a qualitative method where the data collection techniques used are interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusions. The results of this study can be seen that the effectiveness of the implementation of the Subsidized Fertilizer program implemented by the Agriculture Service of Siak Regency has not been effective, especially in terms of the accuracy of program targets that have not been maximized. However, the indicators that have been achieved are program socialization. It is hoped that in the future the government of the Siak Regency Social Service will optimize the Subsidized Fertilizer program to achieve the goal of increasing the ability of farmers to purchase fertilizers in appropriate quantities according to the recommended dose of location-specific balanced fertilization and the final goal of increasing agricultural productivity and production in order to improve national food security.